2018
DOI: 10.1038/nature25989
|View full text |Cite|
|
Sign up to set email alerts
|

Maximizing and stabilizing luminescence from halide perovskites with potassium passivation

Abstract: Metal halide perovskites are of great interest for various high-performance optoelectronic applications. The ability to tune the perovskite bandgap continuously by modifying the chemical composition opens up applications for perovskites as coloured emitters, in building-integrated photovoltaics, and as components of tandem photovoltaics to increase the power conversion efficiency. Nevertheless, performance is limited by non-radiative losses, with luminescence yields in state-of-the-art perovskite solar cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
1,534
2
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,477 publications
(1,632 citation statements)
references
References 36 publications
57
1,534
2
11
Order By: Relevance
“…As shown in Figure S4 in the Supporting Information, the compact shape and smooth surface of perovskite lamella Adv. [20] It is evidenced that light illumination can induce an improvement in photophysical properties of the 3.5 mol% K + perovskite, while in the 0 mol% K + perovskite light illumination leads to inferior PL behavior, which is intimately correlated with solar cell performance. 2019, 9,1901016 specific spatial distribution, tracing out the K/Br-rich grains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure S4 in the Supporting Information, the compact shape and smooth surface of perovskite lamella Adv. [20] It is evidenced that light illumination can induce an improvement in photophysical properties of the 3.5 mol% K + perovskite, while in the 0 mol% K + perovskite light illumination leads to inferior PL behavior, which is intimately correlated with solar cell performance. 2019, 9,1901016 specific spatial distribution, tracing out the K/Br-rich grains.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has rapidly progressed from 3.8% to exceed 24.2% during the past decade. [20] In this point of view, potassium cations are mainly distri buted at the surfaces and grain boundaries by forming KI/KBr to immobilize the surplus mobile halide ions and vacancies, [3] which is contradictory to the interstitial occupancy of K + in the perovskite lattice. Meanwhile, Abdi-Jalebi et al demonstrated that K + doping in mixed perovskites reduces nonradiative losses and photoinduced ion migration in perovskite films by decorating the surfaces and grain boundaries with passivating potassium halide layers.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Theoretically speaking, it may produce a PCE of more than 30% with an improvement in ll factor (FF) and open circuit voltage (V oc ). [12][13][14] The incorporation of additive has been recognized as an efficient methodology to increase the performance of PSCs. [15][16][17][18] Previous reports have demonstrated that incorporating diiodooctane (DIO), NH 4 Cl 19,20 and alkylammonium iodides 11,21 can increase the performance of PSC devices.…”
Section: Introductionmentioning
confidence: 99%
“…[88] Luo et al [88] implemented nano-XRF to show how Cs homogenized the A-site cation chemistry and how Cs + ions helped grain growth in a mixed perovskite (Figure 14A). [124,125] However, the mechanisms that drive these performance and long-term durability enhancements were not very well understood. [92] Third, K has been used to improve the long-term stability of PSCs.…”
Section: A-site Cation and Homogeneitymentioning
confidence: 99%